IMPLEMENTASI CLINICAL SUPERVISION DALAM MENYELESAIKAN PROBLEMATIKA PEMBELAJARAN - Aurelia, Velda Atha; Maunah, Binti; Mutohar, Prim Masrokan (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
PLearning problems are anything that causes problems so that the objectives of learning are not achieved properly. This is caused by something related to the learning components themselves, one of the factors comes from the teacher who plays an important role in a learning activity. To resolve problems regarding learning problems experienced by teachers, supervision is needed. Clinical supervision is the answer to overcoming teacher problems in learning. Clinical supervision is the same as diagnosing sick people, so teachers also receive a diagnosis in the learning process. The purpose of writing this scientific journal is to describe the implementation of Clinical Supervision in Resolving Learning Problems. This journal uses a library analysis method, namely by utilizing library sources to obtain theories and limiting activities to library collection materials and other factual references. The results of this research showed that in the implementation of Clinical Supervision, supervisors were carried out to identify teachers' problems or problems in relation to the teaching and learning process by means of observation which was much more acceptable to teachers through 3 stages, namely the initial meeting, class observation and final meeting.